2011
DOI: 10.1186/1550-2783-8-s1-p4
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of two popular weight loss programs in women I: body composition and resting energy expenditure

Abstract: 42 sedentary women (33±7 yrs, 164±7 cm; 93±19 kg; 46±7% body fat, 35±6 kg/m2) were randomized to participate in the Curves (C) or Weight Watchers (W) weight loss programs for 16‐wks. Participants in the C program followed a 1,200 kcal/d diet for 1‐wk and 1,500 kcal/d diet for 3 wks (30:45 CHO:PRO). Subjects then ingested 2,000 kcals/d for 2‐wks (45:30 CHO:PRO) and repeated this diet while participating in the Curves with Zumba program 3‐d‐wk. Remaining subjects followed the W point‐based diet program, received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…In the present study, 12 weeks of walking, resistance training, and the maintenance of a modest decrease in energy intake promoted significant weight loss (−1.88 [−0.6, −3.2] kg, p = 0.007), fat loss (−2.4 [−1.3, −3.5] kg, p < 0.001), and a reduction in body fat percent (−2.43 [−1.3, −3.5] %, p < 0.001) while increasing FFM (0.54 [0.06, 1.01] kg, p = 0.03) in both treatment groups. These findings are consistent with our prior research [10,36,[72][73][74][75][76][77] and others [78][79][80][81][82][83] that showed that this type of exercise and dietary intervention promotes a reduction in energy intake and fat loss while maintaining or increasing muscle mass and/or REE. However, beyond a trend toward a greater reduction in energy and a significant reduction in fat intake, supplementation with fucoxanthin did not promote a significant increase in REE or greater weight and fat loss compared with those ingesting a placebo.…”
Section: Primary Outcomessupporting
confidence: 93%
“…In the present study, 12 weeks of walking, resistance training, and the maintenance of a modest decrease in energy intake promoted significant weight loss (−1.88 [−0.6, −3.2] kg, p = 0.007), fat loss (−2.4 [−1.3, −3.5] kg, p < 0.001), and a reduction in body fat percent (−2.43 [−1.3, −3.5] %, p < 0.001) while increasing FFM (0.54 [0.06, 1.01] kg, p = 0.03) in both treatment groups. These findings are consistent with our prior research [10,36,[72][73][74][75][76][77] and others [78][79][80][81][82][83] that showed that this type of exercise and dietary intervention promotes a reduction in energy intake and fat loss while maintaining or increasing muscle mass and/or REE. However, beyond a trend toward a greater reduction in energy and a significant reduction in fat intake, supplementation with fucoxanthin did not promote a significant increase in REE or greater weight and fat loss compared with those ingesting a placebo.…”
Section: Primary Outcomessupporting
confidence: 93%
“…Obesity is a major public health crisis in the United States [1]. More than two-thirds of the U.S. population is either overweight or obese [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…We then decided to compare this exercise and diet intervention approach to other popular diet intervention programs. In the first comparative effectiveness study [69], 51 sedentary women were randomized to participate in the Curves ® (C) or Weight Watchers ® (W) weight loss programs for 16weeks. Participants in the C program followed a 1,200 kcal/day diet for 1-week and 1,500 kcal/day diet for 3-weeks (30:45:25%).…”
Section: Comparison Effectiveness Studiesmentioning
confidence: 99%